Pre‐pregnancy iodized salt improved children's cognitive development in randomized trial in Ethiopia. Issue 3 (7th January 2020) - Mohammed, Husein; Marquis, Grace S.; Aboud, Frances; Bougma, Karim; Samuel, Aregash
Abstract: The overarching Ethiopia project examined the effects of early market introduction of iodized salt on the growth and mental development of young children. Sixty districts were randomly assigned to intervention (early market access to iodized salt) or control (later access through market forces), and one community per district was randomly chosen as the sampling unit. For this project, 22 of the districts were included. The participants were 1, 220 pregnant women who conceived after the intervention began. When their children were 2 to 13 months old, field staff collected information on household sociodemographic status and iodized salt intake, child stimulation, maternal depression symptoms, children's diet, anthropometry, urinary iodine concentration (UIC), hemoglobin, and mental development scores (Bayley III scales). Fewer mothers prepartum (28% vs. 41%, p < .05) and their children (13% vs. 20%, p < .05) were iodine deficient (UIC <50 μg/L) in the intervention compared with the control group. The intervention children had higher cognitive scores (33.3 ± 0.3 vs. 32.6 ± 0.3; Δ = 0.6; 95% CI [0.0, 1.3]; d = 0.17; p = .01; 4 IQ points) than their controls. The other Bayley subscale scores did not differ from control children. The intervention group had a higher child stimulation (22.7 ± 0.2 vs. 22.1 ± 0.2; Δ = 0.5; 95% CI [0.02, 0.89]; d = 0.17; p = .01) but not growth indicators (weight‐for‐age z score, length‐for‐age z score, and weight‐for‐length z score: −1.1 ± 0.1 vs. −1.1 ± 0.1, −1.7 ± 0.1 vs. −1.7 ± 0.1; −0.2 ± 0.1 vs. −0.1 ± 0.1, respectively, all p > .05) compared with their controls. Iodized salt intake improved iodine status of both pregnant women and their children and also child cognitive development.